THE PECULIARITIES OF USING ROLE-PLAYS IN TEACHING FOREIGN LANGUAGES - Bahrieva Nargiza Ziyoyevna (International Journal of Innovations in Engineering Research and Technology, 2021)
Thearticle discusses role-play as a methodological technique that belongs to the group of active ways of teaching practical knowledge of a foreign language. The basic didactic structures of role-plays for young educators are analyzed. And also main structural components of the teaching role plays are highlighted based on the main characteristic features of all role plays in language learning.